Strategi Guru dalam Meningkatkan Motivasi Kemampuan Membaca di Masa Pandemi Kelas I SDI Al-Hakim Boyolangu - Fatin Afifah; Adi Wijayanto; Narulita Evia Riskhayanti (MISOOL: Jurnal Pendidikan Dasar, 2022)
The ability to read must be possessed by every student as a necessity in obtaining knowledge and information. Without having the ability to read, students will find it difficult to follow the learning process. This study aims to determine the strategies used by teachers in increasing the motivation to read grade 1 students during the pandemic. The research approach used is qualitative with a descriptive research type. Data collection techniques using observation, interviews, and documentation. The research was conducted at SDI Al-Hakim Boyolangu, and the subjects of this research were the teachers and students of grade 1 SDI Al-Hakim Boyolangu. The data that has been obtained is analyzed using reduction, then presented, then drawn conclusions. The results obtained that: 1) the teacher uses an interactive and bottom-up learning model. 2) the learning method used is the syllable method for students who are not yet proficient at reading. 3) the learning media used by the teacher to increase the motivation for reading skills of grade 1 students are flash cards and blackboards